Analysis of Vibration When Application of Progressive Grinding Wheels - Steiningerova, Jana; Neslusan, Miroslav; Nemeth, Stefan (Communications - Scientific letters of the University of Zilina, 2007)
This investigation was undertaken to compare the performance of grinding wheels containing newly developed “seeded gel” aluminum oxide abrasive with the wheels containing conventional monocrystalline aluminum oxide. The experiments were carried out on the surface grinder BPH 20 over a wide range of removal rates with two grinding wheels on hardened bearing-steel specimens. It was found that the wheels containing “seeded gel” abrasive required less grinding power and gave higher grinding stability than monocrystalline abrasive wheels of the same grade with better surface waviness. The potential improvement in productivity using the “seeded gel” abrasive wheels was estimated. Optimal removal rates with the SG wheel are higher than the one for conventional monocrystalline aluminum oxide.